Model Comparison of Covid-19 in Lampung Indonesia - Widayanti, Tika; Nisa, Khoirin; Yulita, Tiyas (KnE Social Sciences, 2023)
The COVID-19 has been pandemic in the world and has resulted in so many deaths due to being infected by the virus, therefore this study aims to determine a suitable model in estimating the number of deaths due to being infected by the COVID-19. This study focus in Lampung, Indonesia. The analysis of the death number was using three methods, there waspoisson regression, negative binomial regression (NBR), and generalized poisson regression (GPR). From the results, three predictor variables have significant effect to the model, there was positive cases of COVID-19, number of poor people, and life expectancy, while population density per km2 has no significant effect. The best estimation model has smallest AIC and BIC values, and the poisson regression method is the best among other methods. Keywords: Poisson Regression, NBR, GPR, COVID-19